Essential Palatal Myoclonus: A Case Report - Pandey, Bhuwan Raj; Acharya, Anup; Singh, Madan Mohan (Journal of Lumbini Medical College, 2017)
Introduction: Palatal myoclonus is a rare condition presenting with clicking sound in ear or muscle tremor in pharynx. There are two varieties: essential and symptomatic. Various treatment options exists ranging from watchful observation to botulinum toxin injection. We have not found any reported case of palatal myoclonus from our country. Here we present a case of essential palatal myoclonus managed with clonazepam. Case report: A young female presented in Ear Nose and Throat clinic with complain of auditory click and spontaneous rhythmic movement of throat muscles for eight months. On examination, there was involuntary, rhythmic contraction of bilateral soft-palate, uvula, and base of tongue. Neurological, eye, and peripheral examination were normal. A diagnosis of essential palatal myoclonus was made. It was managed successfully with clonazepam; patient was still on low dose clonazepam at the time of making this report. Conclusion: Essential palatal myoclonus can be clinically diagnosed and managed even in settings where MRI is not available or affordable. Journal of Lumbini Medical College Vol 5, No 1, Jan-June 2017, Page: 41-43 DOI: https://doi.org/10.22502/jlmc.v5i1.124